level of achievement motivation among Jerusalem district school teachers, and its relationship to some demographic variables - Halawani, Shaima Mohammad Fahmi (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the level of achievement motivation among Jerusalem district school teachers, and its relationship to some demographic variables: (gender, age, educational qualification, years of experience, and place of residence). To achieve the objectives of the study the researcher used the descriptive and analytical method, The study population consisted of all the teachers in the schools of the Jerusalem District, who numbered (1150) teachers, and the study sample consisted of (135) respondents from teachers of the basic stage, selected by the simple random sample method, The results of the study indicated that the total score of the teachers motivation level came with a medium degree with an arithmetic average of (4.15), and the dimension of (need for achievement) came with a high degree and with an arithmetic average of (4.37), The dimension (the need to control) came with a medium degree, with a mean of (4.18). While the (need to belong) dimension came with a medium degree, with an arithmetic mean of (3.90), There are also statistically significant differences in the motivation averages of teachers in Jerusalem due to the gender variable on the total score, and other dimensions, in favor of females. There are no statistically significant differences in the motivation averages of teachers in Jerusalem according to the variable of years of experience, academic qualification, and place of residence.
Keywords: achievement motivation; Jerusalem school teachers